2022
DOI: 10.1302/2046-3758.115.bjr-2021-0334.r1
|View full text |Cite
|
Sign up to set email alerts
|

The role of AGEs in pathogenesis of cartilage destruction in osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative disease resulting from progressive joint destruction caused by many factors. Its pathogenesis is complex and has not been elucidated to date. Advanced glycation end products (AGEs) are a series of irreversible and stable macromolecular complexes formed by reducing sugar with protein, lipid, and nucleic acid through a non-enzymatic glycosylation reaction (Maillard reaction). They are an important indicator of the degree of ageing. Currently, it is considered that AGEs accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Diabetes mellitus (DM, hyperglycemia) and OA interact at local and systemic levels. Local effects of ROS and AGEs were implicated in cartilage damage [74]. Studies included in the present review revealed that delphinidin, a potent antioxidant, and AGEs affect the viability of human chondrocyte cells via autophagy [10,20].…”
Section: Discussionmentioning
confidence: 73%
“…Diabetes mellitus (DM, hyperglycemia) and OA interact at local and systemic levels. Local effects of ROS and AGEs were implicated in cartilage damage [74]. Studies included in the present review revealed that delphinidin, a potent antioxidant, and AGEs affect the viability of human chondrocyte cells via autophagy [10,20].…”
Section: Discussionmentioning
confidence: 73%
“…These irreversible AGEs, formed through non-enzymatic glycation reactions (Maillard reaction), stand as crucial indicators of aging, implicated as a mechanistic basis for age-induced OA, highlighting their role in inducing and accelerating OA's pathological changes. AGEs' influence on chondrocyte behavior includes increased apoptosis rates, MMP13 expression, and inhibition of chondrocyte autophagy, mediated through intricate pathways involving phosphorylation of key proteins and modulation of signaling cascades [ 146 , 147 ].
Fig.
…”
Section: Glycosylation and Glycation Abnormalities In Oamentioning
confidence: 99%
“…ACTR2A, activin receptor 2 A; ACTR2B, activin receptor 2B; ALK, activin-like kinase; TGFβRII, transforming growth factor β receptor type II; BMPR2, bone morphogenetic protein receptor type 2. cartilage, while the degradation of aggrecan renders the chondrocytes inelastic, further leading to the destruction of cartilage. 27,28 Biver et al 13 found that an increase in BMP levels in cartilage stimulated the excessive synthesis of chondrocyte matrix and MMP-13, which can promote tissue repair and stimulate cartilage degeneration to induce OA, respectively. Mechanical damage to joints can induce articular cartilage to express terminal hypertrophy markers such as MMP-13 and lead to the damage of collagen network, 29 therefore leading to OA.…”
Section: The Structure Of Articular Cartilage Under Physiological Con...mentioning
confidence: 99%